Impact of Inadequate Number of Lymph Nodes Examined on Survival in Stage II Colon Cancer - Wu, Qi; Zhang, Zhiyuan; Chen, Yijiao; Chang, Jiang; Jiang, Yudong; Zhu, Dexiang; Wei, Ye (Frontiers in Oncology, 2021)
Background: Inadequate number of lymph nodes examined was not uncommon. We aimed to evaluate the clinical role of inadequate number of examined lymph nodes in stage II colon cancer. Methods: Using the chi-square test, all the variables obtained in our study were compared based on whether patients had enough (≥12) examined lymph nodes. Kaplan-Meier analysis was used for overall survival (OS) survival analysis and the log-rank test was applied to compare different N stage with the total number of examined lymph nodes. Multivariate analysis was carried out by creating a Cox proportional hazards model to assess the prognostic role of different variables. Results: In total, 80296 colon cancer patients were recruited for our study. N0 stage with ＜ 8 lymph nodes examined would present with worse prognosis compared to stage N1 (5-year OS rates, 51.6% VS. 57.1%, P < 0.001). Multivariate analyses indicated that OS of N0 stage with < 8 examined lymph nodes was similar to that of N1 stage after adjusting for other well- known prognostic factors [hazard ratios (HRs) = 1.051, 95% confidence intervals (CIs) = 1.014 - 1.090, P = 0.018; Table 3]. Conclusions: N0 stage with less than 8 examined lymph nodes presented with similar OS compared to that of N1 stage in stage II colon cancer. More intense treatments may be required for stage II colon cancer with less than 8 examined lymph nodes.